Expression of gene encoding Theileria parva enolase in Escherichia coli JM103 strain - Celik, Venhar; Icen, Irmak; Pelle, Roger; Munzuroglu, Omer; Geckil, Hikmet (Elsevier Sci Ltd, 2011)
[Abstract Not Available]
European Biotechnology Congress -- SEP 28-OCT 01, 2011 -- Istanbul, TURKEY